Development of the NurseTrack Application on Nurse Performance Assessment - Ari Sukma Nela; Armen Patria; Prayetni (CV. CENDIKIA JENIUS INDONESIA, 2026)
Background: This study used a Research and Development (R&D) design with the Borg & Gall model approach, which included needs analysis, application design, expert validation, limited testing, and implementation. The research population included all nurses working in the inpatient ward. The sampling technique used total sampling in the limited testing stage and proportionate sampling in the implementation stage. The research instruments consisted of a nurse performance assessment questionnaire, an expert feasibility test sheet, and a user satisfaction questionnaire. Data analysis used a paired t-test to measure the difference in performance before and after using the application Methods: This study used a Research and Development (R&D) design with the Borg & Gall model approach, which included needs analysis, application design, expert validation, limited testing, and implementation. The research population included all nurses working in the inpatient ward. The sampling technique used total sampling in the limited testing stage and proportionate sampling in the implementation stage. The research instruments consisted of a nurse performance assessment questionnaire, an expert feasibility test sheet, and a user satisfaction questionnaire. Data analysis used a paired t-test to measure the difference in performance before and after using the application Results: The results of the study show that the NurseTrack application was rated “highly feasible” by content experts and technology experts, with an average feasibility score of 89%, and 87% of respondents stated that the application facilitates performance monitoring, improves assessment transparency, and assists in continuous evaluation. Conclusion:This study concludes that the NurseTrack application is effective as a technological innovation in nursing management to improve the objectivity, efficiency, and accuracy of nurse performance assessments. This application is recommended for widespread implementation as part of the digitization of nursing human resource management in hospitals